Rosenfeld’s Staining: A Valuable Tool for In Vitro Assessment of Astrocyte and Microglia Morphology - Alana Alves Farias; Ana Carla dos Santos Costa; Jéssica Teles Souza; Érica Novaes Soares; Cinthia Cristina de Oliveira Santos Costa; Ravena Pereira do Nascimento; Silvia Lima Costa; Victor Diogenes Amaral da Silva; Maria de Fátima Dias Costa (Neuroglia)
In homeostasis, the glial cells support pivotal functions, such as neuronal differentiation, neuroprotection, nutrition, drug metabolism, and immune response in the central nervous system (CNS). Among these cells, astrocytes and microglia have been highlighted due to their role in the pathogenesis of several diseases or due to their role in the defense against several insults (ex., chemicals, and pathogens). In Vitro cytological analysis of astrocytes and microglia has contributed to the understanding of the role of morphological changes in glial cells associated with a neuroprotective or neurotoxic phenotype. Currently, the main tools used for the investigation of glial cell morphology in culture are phase contrast microscopy or immunolabeling/fluorescence microscopy. However, generally, phase contrast microscopy does not generate images with high resolution and therefore does not contribute to visualizing a single cell morphology in confluent cell cultures. On the other hand, immunolabeling requires high-cost consumable antibodies, epifluorescence microscope or confocal microscope, and presents critical steps during the procedure. Therefore, identifying a fast, reproducible, low-cost alternative method that allows the evaluation of glial morphology is essential, especially for neuroscientists from low-income countries. This article aims to revise the use of Rosenfeld’s staining, as an alternative low-cost and easy-to-reproduce method to analyze astrocytic and microglial morphology in culture. Additionally, it shows Rosenfeld’s staining as a valuable tool to analyze changes in neural cell morphology in toxicological studies.